Experimental study and finite element analysis of POZD and large-rupture-strain FRP for improving the protective performance of civil air defense wall. (December 2022) - Shi, Chenglong; Zhang, Jigang; Wang, Xiangying; Liu, Feifei; Chen, Wenli; Ma, Zhehao; Liang, Haizhi; Zhao, Yang
Abstract: In order to reduce and prevent the damage of fragments generated by impact load to personnel, buildings and protective equipment, it is very important to improve its impact resistance and anti-collapsing ability. In this paper, the out-of-plane large-mass pendulum impact test and numerical analysis were carried out for the first time on the protective performance of the POZD new material and large-rupture-strain FRP in the civil air defense wall. The research results show that spraying POZD coating or pasting large-rupture-strain FRP on the civil air defense wall significantly reduces the damage degree of the wall. When the impact height of the pendulum is 0.4 m, the maximum displacement of the wall at mid-span was reduced by 40.5 %, the peak strain of the steel bar at the impact center is reduced by 79.2 %, and the residual strain of the concrete is reduced by up to 60 %, and the bending stiffness and deformation capacity of the walls were improved. The POZD coating can wrap concrete fragments, avoid large-scale collapse damage, and improve the wall's ability to sustainably resist impact loads. The double-sided sprayed POZD coating of the civil air defense wall has a significant effect on improving the impact resistance and preventing the splash of fragments. Even with the increase of pendulum impact height and number, the peak impact force decreases from 3110 kN for the first time to 2465 kN for the third time, which is only 20.7 % lower, it can resist the larger impact load out-of-plane. Under the action of strong dynamic load, the POZD coating can absorb the impact energy by taking advantage of its high tensile elongation at break, which has a good anti-collapsing effect and improves the overall airtightness of the structure. Finally, the failure modes and failure characteristics of the wall obtained through the experiments in this paper provide the failure evaluation criteria for the existing civil air defense walls.